2007
DOI: 10.3923/pjbs.2007.910.914
|View full text |Cite
|
Sign up to set email alerts
|

Salt Stress Inhibits Germination and Early Seedling Growth in Cabbage (Brassica oleracea capitata L.)

Abstract: Salinity induced inhibition in germination and early stages of cabbage (Brassica oleracea capitata L.) [two varieties (autumn cabbage and spring cabbage)] were measured in response to increasing NaCl concentration. The salinity (NaCl) concentrations in solution were 0 (control), 4.7, 9.4 and 14.1 dS m(-1). Different concentrations of salt stress had considerable effect on germination, germination rate (1/t50, where t50 is the time to 50% of germination), root and shoot lengths, root, shoot and plant fresh weig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(27 citation statements)
references
References 16 publications
1
19
0
1
Order By: Relevance
“…Chl and carotenoids can be degraded due to high sodium ion toxicity during salt stress. Several crops have been reported of having reduced Chl a and Chl b concentrations upon salinity stress, e.g., cabbage ( Brassica oleracea capitata L.), sunflower ( Heliantus annuus L.), wheat ( Triticum aestivum L.), and sugarcane 18 - 24 . The extent of reduction of the pigment content depends on the salt tolerance of the plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Chl and carotenoids can be degraded due to high sodium ion toxicity during salt stress. Several crops have been reported of having reduced Chl a and Chl b concentrations upon salinity stress, e.g., cabbage ( Brassica oleracea capitata L.), sunflower ( Heliantus annuus L.), wheat ( Triticum aestivum L.), and sugarcane 18 - 24 . The extent of reduction of the pigment content depends on the salt tolerance of the plant species.…”
Section: Discussionmentioning
confidence: 99%
“…Inhibition of seed germination and shoot and root was noticed as a result of sodium chloride treatments in rice and cabbage (Jamil et al, 2007;Sheng et al, 2011). Also, Razzaque et al (2009) have found an adverse effect of salt on plant height, root, shoot and dry matter of seven rice genotypes.…”
Section: Introductionmentioning
confidence: 98%
“…The retardation of the radicle growth under salt stress may be due to the reduction in the turgor of the radicle cells (Bewley &tions of NaCl reduced radicle and hypocotyls length. Also, Jamil et al (2007), mentioned that using NaCl at concentrations between 4.7 to 14.1 dSm -1 inhibited seed germination and seedling growth of two varieties of cabbage. Young et al (2005) and Zhao et al (2009).…”
Section: Wwwccsenetorg/jasmentioning
confidence: 99%
“…Abbas et al (2013) demonstrated that the percent germination, shoot and root length, and dry weight of rice ( Oryza sativa ) were reduced with increasing levels of NaCl. Similarly, in dicotyledonous cabbage ( Brassica oleracea ), seed germination and the growth of roots and buds were also inhibited under salt stress (Jamil et al, 2007). Therefore, salt tolerance at the germination stage is critical for the successful growth of plants in saline conditions.…”
Section: Introductionmentioning
confidence: 99%